Neurodevelopment in Children Exposed to Zika in utero: Clinical and Molecular Aspects - Schuler-Faccini, Lavínia; del Campo, Miguel; García-Alix, Alfredo; Ventura, Liana O.; Boquett, Juliano André; van der Linden, Vanessa; Pessoa, André; van der Linden Júnior, Hélio; Ventura, Camila V.; Leal, Mariana Carvalho; Kowalski, Thayne Woycinck; Rodrigues Gerzson, Lais; et al. (Frontiers in Genetics, 2022)
Five years after the identification of Zika virus as a human teratogen, we reviewed the early clinical manifestations, collectively called congenital Zika syndrome (CZS). Children with CZS have a very poor prognosis with extremely low performance in motor, cognitive, and language development domains, and practically all feature severe forms of cerebral palsy. However, these manifestations are the tip of the iceberg, with some children presenting milder forms of deficits. Additionally, neurodevelopment can be in the normal range in the majority of the non-microcephalic children born without brain or eye abnormalities. Vertical transmission and the resulting disruption in development of the brain are much less frequent when maternal infection occurs in the second half of the pregnancy. Experimental studies have alerted to the possibility of other behavioral outcomes both in prenatally infected children and in postnatal and adult infections. Cofactors play a vital role in the development of CZS and involve genetic, environmental, nutritional, and social determinants leading to the asymmetric distribution of cases. Some of these social variables also limit access to multidisciplinary professional treatment.